Efficacy of Yoga to Improve Balance and Reduce Fall in Community Dwelling Elders WHO Are at Risk of Fall - Dr. Snehal Chincholkar (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Identification of older adults who are at a risk for falling is a vital medical concern. Falls are common events in the lives of older people and can result in a range of adverse outcomes, from minor bruises to fractures, disability, dependence and death. With age, balance abilities decline and become harder to control, which results in an increased risk of falling, even in the absence of specific neurological or musculoskeletal problems. TUG a simple screening test for measuring the probability for fall among elders and Modified fall efficacy scale for determination of measuring fear of falling. Yoga, with its gentle movements, can address known fall risk factors (poor balance, impaired mobility, reduced strength and flexibility) and focus on increased awareness and proprioception, resulting in decreased fear of fall and improved balance in older adults. Therefore, the purpose of this study is to investigate the effect of yoga to improve balance and reduce fall in community dwelling elders at risk of fall. 100 subject were taken with consent and 6weeks protocol Yoga was given. Yoga Asanas were uttkatasana, tadasana, vrukshasana, trikonasana, virbhadrasana (position 1 & 2). First 3 week Yoga exercises were performed with support of walls and chair.(in the modified form). In the next 3 weeks yoga exercises were progressed by performing without support and increasing the hold time of asanas. Results obtain were that the functional mobility (TUG), and fear of falling (MFES) showed more improvement. Therefore Yoga is effective to improve balance and reduce risk of fall.